Inovasi Pemetaan Talenta Siswa Menggunakan Platform Interaktif Studi Kasus : ( SMK XYZ ) - Sri Hartati; Musrifah; Rito Cipta; Rina Apriliani; Eka Primus; Fathir (Pusat Riset dan Inovasi Nasional, 2025)
Mapping student talents is an important step in supporting the development of potential and early career planning. However, conventional approaches such as written tests and manual observations are often considered inefficient and less engaging for students. This community service activity introduces an innovation in the form of an interactive platform specifically designed to map student talents in a more dynamic and enjoyable way. The platform combines educational elements with digital interaction, where students engage in a series of activities such as adaptive quizzes, case study simulations, and interest-based challenges. The data obtained in real-time is then analyzed to generate student potential profiles based on interests, cognitive tendencies, and learning styles.The results of implementation by a lecturer from another university who has applied one of these interactive platforms show that using such a platform increases student participation and provides a more accurate depiction of student talents compared to traditional methods. This innovation is expected to become an effective digital solution for schools in conducting continuous, data-driven assessments of student potential.